The Productivity of NHLBI‐Funded Obesity Research, 1983‐2013 - Nicastro, Holly L.; Belter, Christopher W.; Lauer, Michael S.; Coady, Sean A.; Fine, Lawrence J.; Loria, Catherine M. (Obesity (Silver Spring, Md.), 2016)
Objective To describe and elucidate the time trends of the academic productivity of NHLBI's obesity‐related research funding via bibliometric analysis of 30 years of NHLBI‐supported obesity‐related publications. Methods In total, 3,545 NHLBI‐funded obesity‐related publications were identified in the Thomson Reuters InCites™ database. Shared references in a community detection algorithm were used to identify publication topics. Characteristics of publications and topical communities were analyzed based on citation count and percentile rank. A percentile rank >90 was considered “highly cited.” Results Obesity‐related publications increased more than 10‐fold over 30 years, whereas NHLBI‐funded publications only increased twofold NHLBI‐funded obesity publications were cited a median of 23 times (IQR 8‐55, range 0‐2,047, mean 52). Thirty percent of these publications were highly cited compared to the expected ten percent. Six topical communities were present in 1983 compared to 16 in 2013. The most highly cited topical areas were sleep (n = 199 publications, 38% highly cited), cardiovascular morbidity and mortality (n = 277, 36%), obesity correlates and consequences (n = 588, 35%), and asthma and inflammation (n = 283, 35%). Conclusions NHLBI‐funded obesity publications have contributed substantially to the obesity literature, with many highly cited. Publications grew in number and topical diversity over 30 years and grew at a faster rate than total NHLBI publications.